Kerangka model interaksi "Hi.Ma.Ji." berasaskan surah al-Nahl ayat 125 dalam membentuk integriti sosial - Baharuddin, Siti Nurbalqis; Abdullah, Muhammad Yusuf Marlon; Ismail, Safinah; Che Alias , Mohd Shariff Al-Faateh (Journal of Islamic, Social, Economics and Development, 2026)
As a pluralistic nation, Malaysia is currently facing complex social cohesion challenges in tandem with the rapid advancement of information technology. Data from the 2022 National Unity Index (IPNas) indicates that the social cohesion score stands at a moderate level (0.629), reflecting the existence of social deficits, particularly within cyberspace. This paper aims to develop an integrity-driven interaction framework by revitalizing the tradition of revealed knowledge through Surah al-Nahl, verse 125, namely al-Ḥikmah (wisdom), al-Maw‘izah al-Ḥasanah (good counsel), and al-Mujādalah (gracious debate). Employing a qualitative approach via content analysis methods including the utilization of contemporary exegeses such as Tafsīr al-Munīr (2005) and Tafsīr al-Sha‘rāwī (1997) this study transforms these da‘wah principles into an innovative interaction model named "Hi.Ma.Ji.". This model is designed to serve as an ethical guide to foster digital social integrity among Malaysian society, thereby addressing polarization and conflict on social media. Ultimately, the findings of this study provide a practical interaction framework to strengthen national harmony in confronting an increasingly challenging digital transformation.